2016
DOI: 10.5539/jas.v8n8p201
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Distribution and Development of Allometric Equations for Non-Destructive Estimation of Carbon Sequestration in Grafted Mango Trees

Abstract: The general equations available/developed for forest/wild mango trees based on measurement of diameter at breast height (DBH) (cannot be used) are not applicable for mango orchards which are predominantly established with grafted plants. Hence allometric equations were developed with destructive sampling of grafted mango trees. The selected parameters showed that allometric parameters were significantly related with age of the trees. The proportion of roots (22%) in grafted mangos was found to be higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…The later process is known as allometric measurements and requires destructive methods to scan specific area of total leaves per plant or tree in the case of LAI [25]. Indirect validation methods are based on proximal instrumentation using the same or similar spectral instrumentation to assess georeferenced sentinel plants at the same angle as the aerial platforms.…”
Section: Vegetation Indices and Validation Processmentioning
confidence: 99%
“…The later process is known as allometric measurements and requires destructive methods to scan specific area of total leaves per plant or tree in the case of LAI [25]. Indirect validation methods are based on proximal instrumentation using the same or similar spectral instrumentation to assess georeferenced sentinel plants at the same angle as the aerial platforms.…”
Section: Vegetation Indices and Validation Processmentioning
confidence: 99%
“…The use of regression models has become a very precise non-destructive method that allows the real leaf area of plants to be estimated from linear measurements of leaf blades (length and width), which are directly correlated with leaf surface area (ZHANG; PAN, 2011). Such methods have been used to estimate leaf area of both cultivated (GANESHAMURTHY et al, 2016;CARVALHO et al, 2017;OLIVEIRA et al, 2017) and forest species (ASSIS et al, 2015;KERAMATLOU et al, 2015;RIBEIRO et al, 2018b;RIBEIRO et al, 2019a;RIBEIRO et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…The fruit accounted for less than 20% of the tree's dry matter at this time, with an increasing investment in the trunk and branches. Oguntunde et al (2011) and Ganeshamurthy et al (2016) explored the changes in tree growth over time for orchards in Nigeria and India and found similar relationships as the ones documented by Davie and Stassen (1997) in South Africa. In Nigeria, the changes in tree canopy volume and leaf area per tree followed sigmoid patterns in trees from two-to thirty-three years of age (Fig.…”
Section: Relationship Between Productivity Tree Growth and Light Intmentioning
confidence: 66%
“…5). The studies of Oguntunde et al (2011) and Ganeshamurthy et al (2016) also demonstrated the strong relationship between leaf area or leaf dry weight per tree and tree canopy volume. Unfortunately, no data on fruit production were mentioned in these investigations.…”
Section: Relationship Between Productivity Tree Growth and Light Intmentioning
confidence: 99%